Afriplex GRTTM extract attenuates hepatic steatosis in an in vitro model of NAFLD. - Kwazi Gabuza; Thendo I Mabuda; Oelfah Patel; Noxolo Khuboni; Ruzayda van Aarde; Sylvia Riedel; Nonhlakanipho F Sangweni; Shantal Windvogel; Rabia Johnson; Christo J F Muller (PLoS ONE, 2024)
Background Currently, it is acknowledged that vitamin E, insulin sensitizers and anti-diabetic drugs are used to manage non-alcoholic fatty liver disease (NAFLD), however, these therapeutic interventions harbour adverse side effects. Pioglitazone, an anti-diabetic drug, is currently the most effective therapy to manage NAFLD. The use of natural medicines is widely embraced due to the lack of evidence of their negative side effects. Rooibos has been previously shown to decrease inflammation and oxidative stress in experimental models of diabetes, however, this is yet to be explored in a setting of NAFLD. This study was aimed at investigating the effects of an aspalathin-rich green rooibos extract (Afriplex GRTTM) against markers of hepatic oxidative stress, inflammation and apoptosis in an in vitro model of NAFLD. Methods Oleic acid [1 mM] was used to induce hepatic steatosis in C3A liver cells. Thereafter, the therapeutic effect of Afriplex GRTTM, with or without pioglitazone, was determined by assessing its impact on cell viability, changes in mitochondrial membrane potential, intracellular lipid accumulation and the expression of genes and proteins (ChREBP, SREBF1, FASN, IRS1, SOD2, Caspase-3, GSTZ1, IRS1 and TNF-α) that are associated with the development of NAFLD. Results Key findings showed that Afriplex GRTTM added to the medium alone or combined with pioglitazone, could effectively block hepatic lipid accumulation without inducing cytotoxicity in C3A liver cells exposed oleic acid. This positive outcome was consistent with effective regulation of genes involved in insulin signaling, as well as carbohydrate and lipid metabolism (IRS1, SREBF1 and ChREBP). Interestingly, in addition to reducing protein levels of an inflammatory marker (TNF-α), the Afriplex GRTTM could ameliorate oleic acid-induced hepatic steatotic damage by decreasing the protein expression of oxidative stress and apoptosis related markers such as GSTZ1 and caspase-3. Conclusion Afriplex GRTTM reduced hepatic steatosis in oleic acid induced C3A liver cells by modulating SREBF1, ChREBP and IRS-1 gene expression. The extract may also play a role in alleviating inflammation by reducing TNF-α expression, suggesting that additional experiments are required for its development as a suitable therapeutic option against NAFLD. Importantly, further research is needed to explore its antioxidant role in this model.